Material analysis of wearabale hyperthermia applicator - Ramasamy, Manoshika (Kansas State University, 2015)
The purpose of this study was to explore printed antennas as an alternative technique for applying hyperthermia treatment. The antenna consisted of a printed ground plane and a thin copper plate. The ground plane was made of silver conductive ink printed on a flexible substrate. The challenge of the printed ground plane was limited conductivity. Multi-layer printing was one of the ways to increase the conductivity of the printed trace. This study examined whether the multiple-layered printings on the ground plane influence the performance of the antenna. The ground plane printed on a flexible substrate was evaluated for its conductivity and capacity to handle the heat energy for the extended time duration at the elevated temperature. This research was conducted in two experimental stages. The first stage of the experiment was designed to test conductivity of the ground plane. Ground planes were printed on a 32.5 mm × 17.0 mm substrate. The thickness and resistance of up to five layers of conductive printing were tested to verify how repeated printing improved the resistance and resistivity. Results showed that the multi-layering technique reduced the resistance of the printed trace, but statistically, the ground plane had no significant improvement in resistance beyond the triple layer printing. With an increase of the thickness, resistivity rather increased after the triple layer printing. The second stage of the experiment was used to assess the performance of the entire antenna. Antennas were fabricated using ground planes with triple and quintuple layers based on resistance and resistivity measurements. The antennas showed an acceptable level of performance in terms of antenna return loss and temperature elevation. The statistical analysis of return loss, power handling capability over the time, and temperature elevation was not significant among the antennas with triple and quintuple layered ground planes. Antennas were able to achieve 42 ˚C within 10 minutes at a 2cm deep location with the return loss of -13.76 dB. Most importantly, experimental results showed that antennas were able to handle 15 watt power without degrading the antenna performance. The antenna showed a successful performance in power handling and reaching the tumor temperature.
Keywords: Breast Cancer; Wearable Hyperthermia Applicator; Conductive Printing; Printed Antenna; Textile Research (0994)